PENGARUH SOSIAL EKONOMI DENGAN KEJADIAN STUNTING PADA BALITA DI DESA KUALU TAMBANG KAMPAR - Dian Wahyuni; rinda fithriyana (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2020)
According to WHO, stunting is a condition of failure to grow. This can be experienced by children who get poor nutrition, have recurrent infections, and have insufficient psychosocial stimulation. Children are said to be stunting when their height growth does not match the world standard growth chart. The 2018 National Health Research (Riskesdas) data processed by Lokadata Beritagar.id shows that 30.8 percent of children under five in Indonesia experience stunting. Based on the Kampar Nutrition Situation Map in 2018 explained that the prevalence of toddlers is very short. In Kampar District it is 6.67% and short toddlers is 13.15%. If you look at the prevalence according to sub-districts in Kampar District, this study is an observational study using a cross-sectional design, using 105 toddlers. The study was conducted in Kualu Village. Bivariate data analysis uses the Quadratic Kai Test. The results showed that some parents in the Toddler Stunting group had a basic education of 102 respondents (92.86%), most had 70 respondents (67.87%) of labor and the income of most of the income below the regional drinking wage (